The transmission dynamic of the COVID 19 outbreak: A predictive dashboard - Muhammad Fahmi, Ahmad Zuber; Norhayati, Rosli; Noryanti, Muhammad (2021)
Predictive model of the susceptible, infectious, death and recovery cases based on the control measures of MCO in Malaysia. Markov Chain Monte Carlo (MCMC) estimation code for epidemiological parameters and basic reproduction number, R0.